Polarization-Insensitive Electromagnetic Metamaterial Design for Multi-Band Energy Harvesting - Hui Zhang; Yang Li; Wenrui Hu; Qibin Lu; Bojun Zhang; Lamar Y. Yang (IEEE Access, 2023)
A multi-band and polarization-insensitive metamaterial is proposed to harvest electromagnetic energy efficiently in three frequency bands. Based on a square resonant ring and cross resonant structure, a metamaterial is designed to achieve high energy harvesting efficiency of 81.2%, 93.3% and 93.5% at 2.45 GHz, 4.0 GHz and 5.8 GHz, respectively. The overall structure consists of an $8× 8$ periodic array of meta-cells with two vias loaded by two $50~Ω $ resistors, an impedance matching network and a rectifier circuit. Results show that the simulated rectification efficiency of rectifier circuit reaches 69.2%, 58.8% and 52.1% at 2.45 GHz, 4.0 GHz and 5.8 GHz, respectively, when the incident power is 5 dBm. The measured harvesting efficiency (RF-DC) is found to be 51.6%, 54.2% and 58.7% with the TE polarization and 50.6%, 53.7% and 58.6% with the TM polarization incidence at the three operating frequency bands, respectively. Although the incident power is reduced to 0 dBm, the energy harvesting efficiency can still reach more than 42% in both TE and TM polarizations. Therefore, it is shown that the energy harvesting system can maintain high efficiency under different polarizations in a wide power range.